Association of Bacterial Vaginosis with Vitamin D in Pregnancy: Secondary Analysis from the Kellogg Pregnancy Study - Powell, Anna Maya; Shary, Judy R.; Louden, Christopher; Ramakrishnan, Vishwanathan; Eckard, Allison Ross; Wagner, Carol L. (American Journal of Perinatology Reports, 2019)
Objective Bacterial vaginosis (BV) is associated with vitamin D deficiency and poor pregnancy outcomes. We studied a nested cohort from a randomized controlled trial to investigate the association between BV and vitamin D concentration in pregnancy.Study Design Subjects with randomly assigned 400 versus 4,400 IU of daily cholecalciferol (vitamin D3) had vaginal swabs collected for Gram staining and Nugent score calculation, as well as plasma 25-hydroxyvitamin D (25(OH)D) measurement at three pregnancy time points.Results Fifty-two (21.2%) of the 245 women included in the analysis were diagnosed with BV at study entry. Women with BV were also more likely to be African American (p < 0.0001) and have lower 25(OH)D concentrations at 22 to 24 weeks' gestation (p = 0.03). There were no differences in pregnancy outcomes of interest within this group compared with the remaining study subjects. In mixed regression modeling, while race (p = 0.001) and age (p = 0.03) were significant predictors of BV prevalence independently, 25(OH)D concentration (p = 0.81), gestational age (p = 0.06), and body mass index (p = 0.87) were not.Conclusion Neither vitamin D deficiency in early pregnancy nor supplementation decreased BV incidence during pregnancy. Pregnancy outcomes (preterm birth and hypertensive disorders of pregnancy) were similar among women with and without BV.
Keywords: bacterial vaginosis; vitamin D supplementation; pregnancy; Gram stain